Methane Storage in a Hydrated Form as Promoted by Leucines for Possible Application to Natural Gas Transportation and Storage. Issue 8 (28th May 2015) - Liu, Yao; Chen, Biyu; Chen, Yulong; Zhang, Shihao; Guo, Weiqi; Cai, Yuanhao; Tan, Bien; Wang, Weixing
Abstract Methane is important in future energy schemes. The main strategies for storing and transporting methane are compression, liquefaction, and physical adsorption in synthetic porous materials. Here, we show that methane can be stored in a hydrated form using natural amino acids such as leucines as effective promoters to form methane hydrate with a high formation rate and a high capacity. In addition, the methane hydrate formed from the L‐leucine solution dissociates without foaming phenomenon. We also showed that the heavier hydrocarbons in natural gas can enhance the promoting effect of L‐leucine.